(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The aim of the research is to clarify the concept of prohibited information and to diagnose the degree of confidentiality in it, as the concept of that information, its characteristics, the scope of its use and the effect of its announcement affect the returns and trading volume. The research problem focuses on measuring the extent of Iraqi banks’ commitment to confidentiality of prohibited information and not disclosing it until the time of its announcement, as well as the extent of the response of the Iraqi Stock Exchange to the content and timing of its announcement. significantly in the success of the banking business. The research Ended with conclusions, the most important of which is that prohibited information is one of the most dangerous sort of information, which in the event of misuse leads to a loss of confidence among investors, shareholders and the public. Information security There should be no diversity in the individuals who use the system and focus on a specific category in dealing with the system.